If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-9*ln(x)-6)/(x^2) = 0
(18/6)*d-9 = 1/6
(x-6)/4 = 0
(24-(4*x))/(3*(8-x)^(2/3))
9/88 = 0
| -20x+10=6+12x | | -3/4x-2=-8] | | -3(-7+2y)-6= | | -38x+7=159 | | (-9ln(x)-6)/(x^2)=0 | | 10=2x(8)+b | | 12s-s=22 | | -32x=-4 | | 3x=(x*x)-40 | | 18/6d-9=1/6 | | p=2k-2w | | 3X+5X-8=15-X | | Y^2+6Y=-20x-89 | | 9x+17(x+1)=17-4x | | X+7=-4x+2 | | -3n+4=n-3n | | 8.5w=-119 | | (2x-y+5z)(2x-y-5z)= | | 9x+(x+1)=17-4x | | 4w-6=11 | | 7y+5x=148 | | (x-6)/4 | | (k-2)x^2-5x+2=0 | | 5(-3-2m)+7m= | | -35x=35 | | 20=2x+1.5y | | 14.82+w=28.82 | | log(4x+3)+log(3)=log(11x+12) | | 2x+6y=168 | | 7/9x3 | | y=-1(-6)+6 | | -141=-6+5(1+7x) |